Reaction of children to dental injection with 27- or 30-gauge needles - DIANA RAM, LAURA HERMIDA B, & ERICA AMIR (IAPD and Blackwell, 2007)
Dentists administer injections on a routine basis. Patients often associate pain with injections and the most anxiety-provoking procedure for both children and adults in dentistry is the local anaesthetic injection.